Publication Trend on Oral Mucositis Induced by Chemotherapy 1978-2023: Bibliometric Analysis - Bakar, Abu; Irham, Lalu Muhammad; Ningrum, Valendriyani (Scripta Medica, 2024)
Oral mucositis (OM) is the oral mucosa inflammation caused by an adverse side-effect of cancer therapy and is expressed as atrophy, enlargement, erythema and ulceration. This bibliometric study aimed to review the publication of OM induced by chemotherapy. The search of bibliometric study using Scopus was performed (accessed on 16 July 2023). In total, 521 documents were retrieved from the Scopus database from 1978-2023. About 2680 authors global were encompassed in writing papers. Investigation of the retrieved papers indicated 424 original articles and 59 review articles. The repossessed papers exhibited top 10 cited articles. The study that obtained the highest number of citations was published in the Cancer in 1999 and received 301 citations (1999-2023). The quotation of this paper was nearly 3-fold higher quotation than those the other ten highest cited scientific papers. The top journal in publishing papers related to the OM stimulated by chemotherapy was the Supportive Care in Cancer, with a total number of papers 41, quadruple than others. This investigation showed that the studies on OM have been more noticeable in the last ten years.
Keywords: Oral mucositis; Chemotherapy; Bibliometrics